The Development of Smart Apps Creator Learning Media to Improve Narrative Writing Skills of Students - Auranisa, Jasmine Diva; Nuryanto, Sukarir (Jurnal Prima Edukasia, 2025)
This study aims to develop Smart Apps Creator (SAC)-based learning media to improve the narrative writing skills of grade IV students at Elementary School 1 Kertek. This research is motivated by the students’ limited ability to write their narratives, which is caused by the lack of interactive and engaging learning media in the Indonesian learning process. The research employed the Research and Development (R&D) method, utilizing the ADDIE model, with 26 grade IV students serving as development subjects and 10 grade V students as evaluators. The results of the study showed that the learning media developed achieved a very good level of feasibility, with validation rates of 93% among material experts, 94% among media experts, and 100% among practitioners for practicality. Effectiveness tests, using both pre-tests and post-tests, showed a significant improvement in students’ narrative writing skills, with an average N-Gain of 0.88. These findings demonstrate that SAC media is effective in enhancing narrative writing skills and can create a more interactive, engaging, and suitable learning environment tailored to the needs and characteristics of elementary school students.